Interactions among Financial Services, Informal Economies and Environmental Performance: Evidence from Developing Countries - Eren, Barış Memduh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study conducts an empirical examination about the roles of financial development, informal economy, fossil fuel and renewable energy consumption on global environmental degradation. Turkey and India are selected as the sample countries to carry out a comparative analysis in the framework of Environmental Kuznets Hypothesis. To this aim, time series procedures are carried out by taking multiple structural breaks into account. Moreover, the study applied the Granger causality test under a vector error correction model to estimate the existence and direction of causality between the variables. The estimated results produced supporting evidence toward the validation of the Environmental Kuznets Curve (EKC) hypothesis. Coefficient estimates indicated that fossil fuel energy consumption, financial development and informal economy in both countries transmit a deteriorating impact on environmental well-being. Conversely, the presented evidence determined that the renewable energy consumption improves the environmental performance by reducing the CO2 emissions. The causality test results suggest that renewable energy consumption is financial development driven in the long run for Turkey and India. Based on the acquired results, this study provides a number of policy recommendations that can be considered to design more efficient economic and financial system in order to achieve energy security and sustainable global environment. Keywords: EKC hypothesis, Financial development, Informal economy, Renewable energy consumption, Environmental degradation, Time series analysis

ÖZ: Bu çalışma, finansal gelişim, kayıt dışı ekonomi, fosil yakıt tüketimi ve yenilenebilir enerji tüketimi değişkenlerinin küresel çevre dezenformasyonu üzerindeki etkileri üzerine ampirik bir inceleme yürütmektedir. Çevresel Kuznets Eğrisi hipotezi çerçevesinde karşılaştırmalı bir analiz yapmak için Türkiye ve Hindistan örnek ülkeler olarak seçilmiştir. Bu amaçla, zaman serisi prosedürleri birden fazla yapısal kırılma göz önünde bulundurularak uygulanmıştır. Ayrıca, değişkenler arasındaki nedensellik ilişkisini ve yönünü tahmin etmek için bir vektör hata düzeltme modeli altında Granger nedensellik testi uygulamıştır. Elde edilen sonuçlar Çevresel Kuznets Eğrisi hipotezini destekleyici kanıtlar sunmaktadır. Katsayı tahminleri, her iki ülkede de fosil yakıt enerji tüketimi, finansal gelişme ve kayıt dışı ekonominin çevresel refah üzerinde kötüleşen bir etki gösterdiğini işaret etmektedir. Buna karşılık, sunulan kanıtlar yenilenebilir enerji tüketiminin CO2 emisyonlarını azaltarak çevresel performansı iyileştirdiğini de göstermektedir. Nedensellik testi sonuçları, yenilenebilir enerji tüketiminin Türkiye ve Hindistan için uzun vadede finansal gelişime bağlı olarak değişkenlik gösterdiğini tespit etmiştir. Elde edilen sonuçlara dayanarak, bu çalışma, enerji güvenliğini ve sürdürülebilir küresel ortamı sağlamak için daha verimli bir ekonomik ve finansal sistem tasarlanabilmesi üzerine bir dizi politika önerisi sunmaktadır. Anahtar Kelimeler: Çevresel Kuznets Eğrisi hipotezi, Finansal gelişim, Kayıt dışı ekonomi, Yenilenebilir enerji tüketimi, Çevresel dezenformasyon, Zaman serisi analizi
Doctor of Philosophy in Finance. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2019. Co-Supervisor: Assoc. Prof. Dr. Korhan Gökmenoğlu, Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Banking and Finance; Financial Services--Informal Economics; Informal sector (Economics); EKC hypothesis; Financial development; Informal economy; Renewable energy consumption; Environmental degradation; Time series analysis